STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN PENDIDIKAN BERBASIS PESANTREN DI SMPN 1 GUNUNG TALANG - Titik Ramadhani (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to describe the implementation of the power strategy by the head of SMP Negeri 1 Gunung Talang in developing pesantren-based education, the implementation of the power strategy in developing pesantren-based education, and the implementation of the Persuasive Strategy and Re-Educative Strategy by the principal of SMP Negeri 1 Gunung Talang in developing pesantren-based education. This type of research is a field research (Field Research) using a qualitative descriptive method. Data was collected by direct observation and interviews submitted to the principal, teacher of the field of study, and several students. The results showed that the implementation of the power strategy by the principal through several ways, namely: the implementation of extracurricular and religious activities, the implementation of orders and prohibitions, the provision of rewards and punishments, Muslim dress, the baliak ka surau program. The implementation of a persuasive strategy by the principal through: establishing good communication with school residents, both teachers, employees, and school officials as well as students and establishing good communication with community members. Normative re-educative strategy by school principals through: disseminating Islamic teachings through students, involving parents in supervising children and involving students and students in Islamic arts activities